2018
DOI: 10.1186/s41938-018-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of defense mechanisms involved in disease resistance of onion blight disease caused by Botrytis allii

Abstract: Botrytis umbel blight caused by Botrytis allii is a major disease that attacks onion crop. In vitro, Trichoderma viride, Penicillium chrysogenum, and Saccharomyces cerevisiae and extract of bitter apple fruits (Citrullus colocynthis) showed antagonistic effect and inhibited the mycelial growth of B. allii. Gas chromatography-mass spectrometry (GC-MS) analysis of bitter apple fruits showed the existence of 37 compounds and their derivatives. Among them, 10 compounds constituted 58.66% of the total analyses. Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…Our study revealed association of increased phenolic content with disease suppression (or increased resistance) to C. capsici. This is in agreement with the previous reports on PGPR Trichoderma viridae, Penicillium chrysogenum and Saccharomyces cerevisiae against blight disease caused by Botrytis allii in onion (Hussein et al, 2018). Many phenolic compounds are known for their antimicrobial activities and function as precursors to structural polymers such as lignin or serve as signal molecules to activate plant defense genes (Dakora, 1996).…”
Section: Resultssupporting
confidence: 93%
“…Our study revealed association of increased phenolic content with disease suppression (or increased resistance) to C. capsici. This is in agreement with the previous reports on PGPR Trichoderma viridae, Penicillium chrysogenum and Saccharomyces cerevisiae against blight disease caused by Botrytis allii in onion (Hussein et al, 2018). Many phenolic compounds are known for their antimicrobial activities and function as precursors to structural polymers such as lignin or serve as signal molecules to activate plant defense genes (Dakora, 1996).…”
Section: Resultssupporting
confidence: 93%
“…Twenty-three isolates of Botrytis spp. were isolated from naturally diseased onion plants showing symptoms of Botrytis Onion Umbel Blight (BOUB), collected from different onion seed producing farms, Assiut, Egypt (Hussein et al, 2018). Onion leaves, showing disease symptoms, were cut in small pieces, sterilized for 2 min in 2% sodium hypochlorite solution then, plated onto Potato Dextrose Agar (PDA) medium and incubated at 27°C.…”
Section: Isolations Of the Causal Pathogensmentioning
confidence: 99%
“…Among the fungal diseases, Botrytis byssoidea and B. allii the causal pathogens of umbel blight of onion are destructive pathogens that involved in a great reduction in the productivity. The umbel blight disease is an important disease that attacks the plant during the production of the seeds and could devastate the unprotected crops up to 70% (Hussein et al, 2018). Spores of B. byssoidea, B. allii, B. porri, and B. squamosa cause infection for seedlings of green and bulb onions (Hussein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E estudos voltados para a cultura da cebola também mostraram uma moderada redução na severidade da doença ferrugem da Botrytis, causada por Botrytis allii, ao se utilizar a S. cerevisiae como um dos tratamentos. E o mesmo ocasionou um aumento significativo no teor total de fenol, indicando um correlação com a redução do desenvolvimento de patógenos, já que tais compostos são substancias tóxicas aos patógenos, outra possibilidade é a resistência ter sido gerada pela alteração do pH do citoplasma da célula vegetal, que é alterado com o aumento do conteúdo fenólico (Khaledi, Taheri, Ta-righi2015;Hussein et al, 2018).…”
Section: Produção De Fitoalexinas Em Cotilédones De Sojaunclassified